First Molecular Identification of Sarcocystis Buffalonis in Goats Worldwide in Misan Governorate, Iraq - Rawaa G. Mohammed, Maytham A. Dragh, Hasan, M. H (Pakistan Journal of Medical & Health Sciences, 2022)
The current study was conducted in Misan Governorate to detect the parasite Sarcocystis spp. by both conventional and molecular methods and to identify the species of this genus in goats as intermediate hosts for multiple species of this parasite. Regarding to the traditional study, the rates of infection with the macroscopic type of Sarcocystis spp. were low and recorded 2% in esophageal samples only in goats. The sizes of macroscopic parasite cysts ranged between 1-10 mm in length and 2-6 mm in width. Infection with the microscopic type of parasite recorded high rates. When comparing the efficiency of the traditional methods used in our study to diagnose the infection of the microscopic type in all of the examined organs isolated from goats, which included the methods of digestion with pepsin, squeezing, trichinoscopy. It was found that the method of digestion with pepsin was the most efficient traditional method for diagnosing the microscopic type of parasite, followed by the trichinoscopy. While the squeezing method recorded the least efficient traditional method for diagnosing Sarcocystis spp. microscopically. The molecular study of Sarcocystis spp. included molecular diagnosis of the parasite’s identity at the species level through gene amplification using polymerase chain reaction (PCR) of the target segment of DNA extracted from the parasite samples of goats for 18S rRNA gene by 120 microscopic samples and 4 macroscopic samples. 87.9% of goat samples, showed positive infection with the 18S rRNA gene; In which 100% of the macroscopic and microscopic samples of the esophagus were recorded, and both animals had a positive infection, while the infection rates for the diaphragm, tongue and heart samples were recorded as 90%, 86.7 and 80%, respectively. The results obtained from sequence analysis of 18S rRNA gene for six samples showed that four microscopic samples of goats (OP474017.1, OP474018.1, OP476699.1 and OP474036.1) were closely related to the Malaysian species; S. capracanis with accession number (KR155191.1) with identity score percentages as 99.50%, 99.01%, 99.76% and 99.13%, respectively. Finally, the two macroscopic samples of goats (OP474061.1 and OP474062.1) were identical with the Egyptian species; S. buffalonis, with accession numbers (KU247913.1) and (KU247913.1) respectively, with a matching percentage of 84.39% and 85.64% respectively. S. buffalonis has identified in goats at the first time globally in present study. Keywords: Sarcocystis buffalonis, Goats, OP474061.1, OP474062.1.